High Power Semiconductor Technology Status and Progresses - Guoyou LIU; Yangang WANG; Xiang LI; Arthur SU; Kongjing LI; Songlin YANG (机车电传动)
The evolution of modern Si based high power semiconductor devices and recent progress of novel device structures,as well as the status of wide bandgap semiconductor materials and devices were presented in this paper. The development and application status of domestic high power semiconductor devices for rail transportation, DC transmission and new energy vehicles were introduced. Finally, the technology challenges and development trends of high power semiconductor technology were discussed.